An observational study on the use of Kahoot! as formative assessment support in higher education - Savira Verdiyanti (Concept : Community Concern for English Pedagogy and Teaching, 2019)
Kahoot! is one of game-based students' response systems (GSRS) that can be used as formative assessment. Formative assessment helps teacher to identify students who struggle to understand the material, to develop skills that they are difficult to acquire, to meet standards competence. Therefore adjustment should be made to the lesson. However, the use of Kahoot! as formative assessment is rarely implemented in Indonesian universities. To fill this void, this study aims to explore the lecture who uses Kahoot! as a formative assessment in their class. The researcher used the construct by Wiliam & Thompson (2007) to characterize formative assessment. The purpose of this study is to reveal more information of the use of Kahoot! as formative assessment in higher education. A qualitative method was presented in this study. The tutor who used Kahoot! as a formative assessment in their class was chosen as the participant. The data were acquired through observation of the tutor. The research findings found out that through Kahoot! as formative assessment, the tutor could develop activities such as clarifying information, doing classroom discussion and also providing feedback. An attractive finding also found that Kahoot! as formative assessment also provides students self-assessment and self-improvement. The result shows that besides being used as a tool for assess students, Kahoot! also provide learners to clarify the question, classroom discussion and also provide feedback, it depends on how the teacher used and forced it. Keywords: Formative Assessment: Kahoot!, Higher Education